Estudios de impacto económico en infraestructuras del transporte: El caso portuario - Ignacio de la Pe\~na Zarzuelo; María Jesús Freire-Seoane; Beatriz López Bermúdez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– Economic Impact Studies in ports are a very widespread tool that began to be developed in the decade of the 60s in the United States. Since then, these studies have been refined, eliminating some of their limitations and restrictions and converging towards a standard methodology that allows comparisons between the effects of different ports. The article analyzes the historical evolution of these studies, indicating the different variants and their methodological limitations and concludes with a summary of the results obtained both internationally and in the particular case of the Spanish port system. It concludes the role that both the size of the port and its traffic structure have in the impacts it generates in terms of employment, added value and productivity.
Keywords: C67; R15; R42; L90; A10; 330; economic impact assement; input - output matrix; Leontief; port economics; port productivity